Post-Transcriptional Regulation of RseA by Small RNAs RyhB and FnrS in Escherichia coli - London, Laricca Y.; Aubee, Joseph I; Nurse, Jalisa; Thompson, Karl M (Frontiers in Molecular Biosciences, 2021)
RseA is the critical central regulator of the Sigma-E-dependent stress response in E. coli and other related bacteria. The synthesis of RseA is controlled at the transcriptional level by several promoters and transcriptional regulators, including Sigma-E itself at two Sigma-E-dependent promoters: rpoEP and rseAP3. The presence of these two independent polycistrons encoding rseA are potentially redundant. We hypothesized that post-transcriptional control of the rseAP3 transcript was necessary to overcome this redundancy. However, to date, nothing is known about the post-transcriptional control of the rseAP3 transcript. We executed a targeted genetic screen to identify small RNA regulators of the rseAP3 transcript and identified RyhB and FnrS as small RNA activators of the RseA P3 transcript. Through genetic analysis, we confirmed a direct interaction which occurs between RyhB and RseA. We also identified negative regulatory potential the 5’ UTR of RseA. RseA 5’ UTR mutations predicted to prevent RyhB-RseA resulted in increased RseA expression. Taken together, this suggests that the 5’ UTR of the RseAP3 prevents optimal expression of RseA, preventing redundancy due to RseA expression from the Sigma-E dependent rpoEP and this is overcome by the stimulatory activity of RyhB and FnrS.